2013
DOI: 10.2174/138161213804581864
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Cancer Metabolic Pathways by the Use of Microarray Technology

Abstract: Cancer metabolism is currently re-evaluated by the research community with the aim to investigate possible opportunities for the development of targeted therapies. Firstly discovered by Warburg et al. in the beginning of the last century, it is now a widely accepted hypothesis that cancer cells possess a severely deregulated form of glycolysis also under aerobic conditions. Accompanied by a deregulated glycolysis is an increasing dependence on glucose and glutamine, this characteristic offers a striking opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 130 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Although several recent studies have demonstrated that n-3 PUFAs may positively affect endothelial dysfunction [ 7 ], a comprehensive evaluation of the endothelial genomic effects exerted by n-3 PUFAs is lacking [ 8 ]. Microarray analysis, the high-throughput genomic tool that allows the simultaneous comparison of thousands of genes, is a useful tool to investigate pathophysiological mechanisms involved in a variety of human diseases, including atherosclerosis [ 9 ], and cancer [ 10 ], in a fashion not biased or restricted by a priori hypotheses. Cluster analysis of resulting data on transcriptional profiling also has the potential of revealing distinctive patterns of gene expression, thus providing novel information on the influence of n-3 PUFAs in vascular pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Although several recent studies have demonstrated that n-3 PUFAs may positively affect endothelial dysfunction [ 7 ], a comprehensive evaluation of the endothelial genomic effects exerted by n-3 PUFAs is lacking [ 8 ]. Microarray analysis, the high-throughput genomic tool that allows the simultaneous comparison of thousands of genes, is a useful tool to investigate pathophysiological mechanisms involved in a variety of human diseases, including atherosclerosis [ 9 ], and cancer [ 10 ], in a fashion not biased or restricted by a priori hypotheses. Cluster analysis of resulting data on transcriptional profiling also has the potential of revealing distinctive patterns of gene expression, thus providing novel information on the influence of n-3 PUFAs in vascular pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Microarray technology has been used to study different types of cancer [16][17][18][19] and is a useful tool to profile gene expression patterns that can facilitate diagnosis, predict response to therapy, find new biomarkers and examine the development of drug resistance in cancer. [20][21][22][23] Recent expression profiling studies from other groups show that HIP-55 is highly expressed in squamous cervical cancer patients and in pancreatic cancer with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%